Development of ceramic‐on‐ceramic implants for total hip arthroplasty - Cai, You‐zhi (Orthop Surg, 2010)
Over the past three decades, alumina ceramic, now in its third/fourth generation, has been markedly improved in terms of its mechanical properties, including purity, grain microstructure, and burst strength. In the clinic, it is particularly suitable for young and for very active patients. This paper discusses the development and characteristics of different kinds of ceramics. In addition, ceramics in the third/fourth generation which are used in total hip arthroplasty clinically are reviewed in detail.